Ed says U said : the eating disorder translator - Alexander, June, 1950- (Jessica Kingsley Publishers, 2013)
A unique resource of information on eating disorders (EDs), this book aims to improve communication between people with EDs and their loved ones by revealing the ED mind set and decoding language choices. Full of everyday examples, it details the common pitfalls and gives invaluable advice on how best to defuse the triggers.